Cultural Identity Transformation of Gaudiya Vaishnavas in Russia - T. V. Yasnaya (Концепт: философия, религия, культура, 2020)
This study of Gaudiya Vaishnavism in Russia focuses on the transformation of its former followers’ worldviews. Major attention is paid to the ways and trends of these changes and, in particular, to the extent of their resilience in Russian cultural landscape today. The Russian Society for Krishna Consciousness (RSKCON) gradually strengthening its position in Russian religious field, its effects are growing in importance and need to be analyzed with the view to previous scientific works. This article outlines the patterns of identity manifestation and realization by Russian Krishnas. The study conducted in 2018 endorsed literature analysis and qualitative methods — an online questionnaire with both close-end and grid-in questions was used for these ends with a non-probability sampling (n=62). The believers and the former believers narratives were analysed so as to illustrate typical patterns and attitudes. The conclusions are as follows. Eclectic identity is what results from engaging with Krishna practices: converting into Hindu, Bengali culture while abandoning traditional Russian culture. However, despite long-lasting practicing of Gaudiya Vaishnava in both cult and mundane aspects, only a minority of former believers still have faith in Krishna after leaving the community. It is therefore revealed that basic customs and patterns — and identity — acquired in the childhood tend to burgeon after quitting Vaishnavism.